Образ России в российском дипломатическом дискурсе (Obraz Rosji w rosyjskim dyskursie dyplomatycznym) Russia in Russian diplomatic discourse - Gaś, Swietłana (Investigationes Linguisticae, 2008)
The aim of this article is to try to present some remarks on one category of words of diplomatic discourse. This category contains words used to create a positive image of Russia, but first of all it creates diplomatic discourse. The author concentrates on conventional, formal aspects of using words in diplomacy only. These words are part of corpus of Polish-Russian Dictionary of Diplomacy projected by author.